The Diversity of Morphological Traits and Seed Metabolomic Composition in Buckwheat Genetic Resources - Petra Hlásná Čepková; Dagmar Janovská; Maria Bernhart; Pavel Svoboda; Michal Jágr; Vladimir Meglič (Plants)
This study examines the impact of environmental conditions on the growth, yield, and biochemical composition of common buckwheat (Fagopyrum esculentum Moench.) across two locations in Central Europe over three consecutive growing seasons (2019–2021). Significant variations in meteorological conditions, including temperature fluctuations and rainfall, were observed between two locations: Austria (AT) and the Czech Republic (CZ). The study highlights the role of these environmental factors in influencing morphological traits such as plant height, leaf dimensions, and 1000-seed weight (TSW), as well as nutritional and bioactive compound content. Buckwheat plants in Austria generally exhibited higher mean values for plant height and TSW compared to the Czech Republic, with significant variability observed across varieties and years. In terms of nutritional quality, crude protein content ranged between 12.56 and 14.71% dw, with the highest protein levels linked to cooler, low-rainfall conditions. The study also investigated phenolic compounds, particularly rutin, which showed a significant increase in content in 2021, likely due to extreme weather conditions. Varieties such as Sweden-1, Tempest, and Zamira exhibited stable, high rutin levels across all years. Overall, this research highlights the complexity of environmental influences on the agronomic and nutritional traits of buckwheat and provides valuable insights for future breeding programs aimed at improving yield and nutritional value under changing climatic conditions.